MINAT BACA BUKU KESEHATAN IBU DAN ANAK DAN KEPATUHAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL : MINAT BACA BUKU KESEHATAN IBU DAN ANAK DAN KEPATUHAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL - Selviya Indriani Putri; Desrinah Harahap; Asih Minarningtyas (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Pregnant women's interest in reading the Maternal and Child Health (MCH) Handbook plays a crucial role in enhancing knowledge about pregnancy and encouraging adherence to prenatal check-ups. The MCH Handbook has been widely distributed as a health education resource for pregnant women. However, its utilization remains suboptimal. Data from the Indonesian Basic Health Research indicate a declining trend in both the ownership and utilization of the MCH Handbook. This study aimed to describe pregnant women's reading interest regarding the MCH Handbook and their adherence to Antenatal Care (ANC) visits. A quantitative descriptive design with a cross-sectional approach was employed. The sample consisted of 101 pregnant women selected using total sampling. Data were collected using a questionnaire on MCH Handbook reading interest and an observation sheet for ANC visit adherence. Adherence was measured against Ministry of Health standards: a minimum of one visit in the first trimester, two visits in the second trimester, and three visits in the third trimester. Data were analyzed using univariate analysis involving frequency distributions and percentages. The results showed that reading interest in the MCH Handbook fell into the high category (98%), with scores of 93,1% for reading duration, 91,1% for reading content, and 96% for self-confidence. Adherence to ANC visits was also in the high category (98%). The study demonstrates that the majority of pregnant women exhibit high levels of reading interest in the MCH Handbook and high adherence to ANC visits.